(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
In this article, the procedure and criteria for evaluating the effectiveness of judges in the Republic of Uzbekistan, their current state, the urgency of their improvement, the experience of foreign countries on the system of evaluating the effectiveness of employees, the suggestions for improving the procedure and criteria for evaluating the effectiveness of judges and their relevance are considered.